2003
DOI: 10.1016/s0020-7292(03)00332-1
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin 1 and leptin in the pathophysiology of intrauterine growth restriction

Abstract: These results suggest the intertwined roles of ET-1 and leptin in the pathophysiology of IUGR. Further studies concerning interaction between these peptides in different pregnancy conditions may provide important information about the actions of ET-1 and leptin on fetal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
3
22
0
3
Order By: Relevance
“…These findings may suggest that catecholamines are involved in the fetal adaptation to both hypoxia and undernutrition. In vascular tissue, expression of the precursor protein for endothelin-1 is increased by hypoxia-inducible factor-1 signaling (22), and the reported increase in fetal plasma endothelin-1 levels in response to hypoxia (1,16) may represent a specific adaptation to a reduced oxygen supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings may suggest that catecholamines are involved in the fetal adaptation to both hypoxia and undernutrition. In vascular tissue, expression of the precursor protein for endothelin-1 is increased by hypoxia-inducible factor-1 signaling (22), and the reported increase in fetal plasma endothelin-1 levels in response to hypoxia (1,16) may represent a specific adaptation to a reduced oxygen supply.…”
Section: Discussionmentioning
confidence: 99%
“…The redistribution of fetal cardiac output during hypoxia may be partially dependent on the reported increased circulating levels of several vasoactive factors, including norepinephrine (14,43) and endothelin-1 (1,19), but may also involve changes in the local vascular responses to these circulating factors. The effects of chronic hypoxia in utero on the regional vascular responses to these vasoconstrictors after birth are not yet known.…”
mentioning
confidence: 99%
“…We chose to measure circulating levels of ET-1, NO x , sFlt-1, and PlGF given previous studies showing their importance in relation to the occurrence of fetal growth restriction and preeclampsia (1,7,8,17,18,25). For example, ET-1 is a potent vasoconstrictor that is known to be elevated in pregnancies complicated by preeclampsia or SGA (7,8), and when its vasoconstrictor actions are inhibited with the use of ET-1 antagonists, hypoxia-associated reductions in uteroplacental blood flow and fetal growth in rat models are completely abolished (27).…”
Section: Discussionmentioning
confidence: 99%
“…In some of these studies, fetal leptin levels per kilogram of fetal weight, as well as fetal leptin levels before 34 weeks of gestation, were not significantly different in IUGR, indicating that leptin secretion is mainly associated with adipose tissue accumulation (61)(62)(63)(64). However, other investigators suggested that low fetal leptin levels in IUGR are associated with reduced placental production, since leptin levels dramatically decrease shortly after birth (73)(74)(75).…”
Section: The Role Of Adipose Tissuementioning
confidence: 98%
“…Several studies demonstrated lower circulating leptin concentrations in IUGR neonates at birth, due to reduced fat mass (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72) and/or decreased placental production (73)(74)(75). In some of these studies, fetal leptin levels per kilogram of fetal weight, as well as fetal leptin levels before 34 weeks of gestation, were not significantly different in IUGR, indicating that leptin secretion is mainly associated with adipose tissue accumulation (61)(62)(63)(64).…”
Section: The Role Of Adipose Tissuementioning
confidence: 99%